Difficulties of Elementary School Teachers in Online Learning during the Covid 19 Pandemic - Amaelia Lediana; Zaka Hadikusuma Ramadan (Jurnal Pendidikan dan Pengajaran, 2022)
The difficulty of elementary school teachers in carrying out online learning during the Covid-19 pandemic is a major problem for the world of education. During the Covid-19 pandemic, people were prohibited from meeting face to face, but learning must continue, so online or online learning is enforced. This study analyzes elementary school teachers' difficulties in carrying out online learning. This study uses a quantitative approach and a descriptive method. The population and the research sample used were school teachers totaling 412 teachers. The sample was obtained using the slovin formula. The data collection technique in this study was a closed questionnaire or questionnaire. This study found that the learning process consisted of 3 stages: planning, implementation, and evaluation—these results were obtained by conducting a survey of teachers by distributing questionnaires. The questionnaire results also found that the teacher's difficulty lies in planning, where a teacher must prepare lesson plans, teaching materials, worksheets, and learning media that follow online learning. The main difficulty lies in the planning that must be under the technology.